International Community Service: Implementation of a Smart Farm Based on Internet of Things in the Salikneta Farm, Philippines - Oscar Karnalim; Bayu Rima Aditya; Mutia Qana'a; Pikir Wisnu Wijayanto; Kathleen B. Aviso; Maria Eda Apple Suplido; Rossevine Artha Nathasya; Robby Tan; Yudha Ginanjar (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2025)
Salikneta Farm is located in Bulacan, Philippines. On that farm, many monitoring tasks were conducted conventionally, which might be labour-intensive and error-prone. Only physical appearance might be considered while monitoring the farm. This international community service developed an IoT-based land monitoring system to help farmers monitor their farms. The IoT system was designed as a suitcase for portability, and it could send the data to a server for further analysis. Upon testing the IoT system, it was then delivered to Salikneta Farm. A workshop was then conducted onsite, covering the IoT system and how to use it in the field. According to 15 participants, the workshop was insightful and helped the participants to understand the IoT system and its usage. The interview with the supervisor of the farm supported this. After the workshop, the IoT system was used on the farm. The supervisor occasionally reported the conditions and consulted on some issues. There was some data reported from the IoT system to a special server. To sum up, the system was considered beneficial for the farm and it is being used.